Structural and Functional Abnormalities in the Islets Isolated From Type 2 Diabetic Subjects - Deng, Shaoping; Vatamaniuk, Marko; Huang, Xiaolun; Doliba, Nicolai; Lian, Moh-Moh; Frank, Adam; Velidedeoglu, Ergun; Desai, Niraj M.; Koeberlein, Brigitte; Wolf, Bryan; Barker, Clyde F.; Naji, Ali; et al. (Diabetes (New York, N.Y.), 2004)
Structural and Functional Abnormalities in the Islets Isolated From Type 2 Diabetic Subjects Shaoping Deng 1 , Marko Vatamaniuk 2 3 , Xiaolun Huang 1 , Nicolai Doliba 2 3 , Moh-Moh Lian 1 , Adam Frank 1 , Ergun Velidedeoglu 1 , Niraj M. Desai 1 , Brigitte Koeberlein 1 , Bryan Wolf 4 , Clyde F. Barker 1 , Ali Naji 1 , Franz M. Matschinsky 2 3 and James F. Markmann 1 1 Department of Surgery, Harrison Department of Surgical Research, Hospital of the University of Pennsylvania, Philadelphia, Pennsylvania 2 Department of Biochemistry and Biophysics, University of Pennsylvania School of Medicine, Philadelphia, Pennsylvania 3 Penn Diabetes Center, Hospital of the University of Pennsylvania, Philadelphia, Pennsylvania 4 Department of Pathology, The Children’s Hospital of Philadelphia, Philadelphia, Pennsylvania Address correspondence and reprint requests to James F. Markmann, MD, PhD, Department of Surgery, Hospital of the University of Pennsylvania, 4th floor Silverstein, 3400 Spruce St., Philadelphia, PA 19104. E-mail: james.markmannatuphs.upenn.edu Abstract Type 2 diabetic subjects manifest both disordered insulin action and abnormalities in their pancreatic islet cells. Whether the latter represents a primary defect or is a consequence of the former is unknown. To examine the β-cell mass and function of islets from type 2 diabetic patients directly, we isolated islets from pancreata of type 2 diabetic cadaveric donors ( n = 14) and compared them with islets from normal donors ( n = 14) matched for age, BMI, and cold ischemia time. The total recovered islet mass from type 2 diabetic pancreata was significantly less than that from nondiabetic control subjects (256,260 islet equivalents [2,588 IEq/g pancreas] versus 597,569 islet equivalents [6,037 IEq/g pancreas]). Type 2 diabetic islets were also noted to be smaller on average, and histologically, islets from diabetic patients contained a higher proportion of glucagon-producing α-cells. In vitro study of islet function from diabetic patients revealed an abnormal glucose-stimulated insulin release response in perifusion assays. In addition, in comparison with normal islets, an equivalent number of type 2 diabetic islets failed to reverse hyperglycemia when transplanted to immunodeficient diabetic mice. These results provide direct evidence for abnormalities in the islets of type 2 diabetic patients that may contribute to the pathogenesis of the disease. GSIR, glucose-stimulated insulin release RIA, radioimmunoassay Footnotes Accepted December 16, 2003. Received May 27, 2003. DIABETES